A health and wellbeing programme for preadolescents in underserved Australian communities: child and stakeholder perspectives. (11th May 2021) - Norman, Jennifer; van Weerdenburg, Katherine; Furber, Susan; Stratten, Maddison; Okely, Anthony D
Summary: Social inequities in childhood affect children's health and development. Active In-Betweens is a weekly, healthy lifestyle and outdoor activity after-school programme, tailor-made for preadolescent children (9–12 year olds), incorporating a strengths-based, trauma-informed, co-designed and place-based approach. This study evaluated the extent to which the programme strategies and activities met the anticipated short- to medium-term programme outcomes during its first year of operation in two socio-economically disadvantaged housing communities in New South Wales, Australia. A qualitative case study used data from semi-structured interviews with child participants ( n = 11) and key stakeholders ( n = 10). A broad range of positive outcomes were described. Children's feedback indicated they had experienced opportunities which facilitated the development of new physical activity skills; new healthy eating experiences and knowledge; positive relationships with peers and facilitators and new connections with neighbourhood programmes and outdoor environments. Stakeholders valued the programme for the positive outcomes they observed among the children and the strong organizational partnerships which resulted. The importance of skilled facilitators to deliver the programme, the engagement of local stakeholders and a long-term commitment to programme delivery, with secure funding to ensure continuity, were clearly identified as integral for effective, sustainable outcomes.